Physical fitness, physical activity and adiposity: associations with risk factors for cardiometabolic disease and cognitive function across adolescence - Ryan A. Williams; Simon B. Cooper; Karah J. Dring; Lorna Hatch; John G. Morris; Feng-Hua Sun; Mary E. Nevill (BMC, 2022)
Abstract Background The cross-sectional associations between physical activity, physical fitness and adiposity with risk factors for cardiometabolic disease (particularly novel ones such as inflammatory cytokines) and cognitive function across the period of adolescence are not well understood. Additionally, novel physical activity metrics that summarise activity volume and intensity in a continuous manner have not been investigated in this context. Therefore, this study investigated the cross-sectional associations between physical activity, physical fitness and adiposity with risk factors for cardiometabolic disease and cognitive function. These associations were compared between younger and older adolescents. Methods Seventy younger (11-12y, 35 girls) and 43 older (14-15y, 27 girls) adolescents volunteered to take part in the study. Physical fitness (multi-stage fitness test, MSFT) and adiposity (waist circumference) were determined, followed 7d later by resting blood pressure, a fasted blood sample (glucose, plasma insulin, IL6, IL10, IL15 and IL-1β concentrations) and a cognitive function test battery. Habitual physical activity was monitored via hip-worn accelerometers over this 7-d period and the average acceleration (activity volume), and intensity gradient (intensity distribution of activity) were determined. Results Average acceleration and intensity gradient were negatively associated with mean arterial blood pressure (β = -0.75 mmHg, p = 0.021; β = -10 mmHg, p = 0.006, respectively), and waist circumference was positively associated with IL-6 concentration (β = 0.03%, p = 0.026), with stronger associations observed in older adolescents. Higher physical fitness (MSFT distance) was positively associated with anti-inflammatory IL-15 concentration (β = 0.03%, p = 0.038) and faster response times on the incongruent Stroop task (β = -1.43 ms, p = 0.025), the one-item level of the Sternberg paradigm (β = -0.66 ms, p = 0.026) and the simple (β = 0.43 ms, p = 0.032) and complex (β = -2.43 ms, p = 0.020) levels of the visual search test, but these were not moderated by age group. Conclusions The present study highlights the important role of physical activity (both the volume and intensity distribution) and physical fitness for cardio-metabolic health. Furthermore, the present study highlights the importance of physical fitness for a variety of cognitive function domains in adolescents, irrespective of age.